One-Year Evaluation of Paliperidone Palmitate 6-Monthly: Satisfaction and Perceived Effectiveness Among Patients, Relatives, and Clinicians - Manchado Perero S; Rodríguez Lorente A; García-Pérez A; Isidro García G; Forcen-Muñoz LA; Ovejero S; Sáez Povedano R; González-Galdámez AL; Iturralde LM; Bonilla MR; Fuentes-Pérez P; Ovejas-Catalán C; et al. (Patient Preference and Adherence, 2025)
Sofía Manchado Perero,1 Ana Rodríguez Lorente,2 Alba García-Pérez,3 Guillermo Isidro García,4,5 Luis Alberto Forcen-Muñoz,6 Santiago Ovejero,1 Rocío Sáez Povedano,7 Ana Luisa González-Galdámez,8 Laura Mata Iturralde,1 Mariluz Ramirez Bonilla,4,5 Paloma Fuentes-Pérez,5 Claudia Ovejas-Catalán,5 Paula Suárez-Pinilla,4,5 Blanca Fernandez Abascal Puente,4,5 Miguel Omaña Colmenares,9 María Pilar Campos-Navarro,2 Enrique Baca-García,1 Ana Lara Fernández,10 Sergio Benavente-López,10 Alberto Raya Platero,11 Miguel Barberán Navalón,9 Sergio Sánchez-Alonso,1 Javier Vázquez-Bourgon,4,5,12 Sofia Pappa,13,14,* Juan Antonio García-Carmona15– 17,* 1Fundación Jiménez Díaz University Hospital, Madrid, Spain; 2Department of Psychiatry, Santa Lucía University Hospital, Cartagena, Murcia, Spain; 3Centre of Mental Health Molina de Segura, Molina de Segura, Murcia, Spain; 4Department of Psychiatry, Marqués de Valdecilla University Hospital, Universidad de Cantabria, Santander, Spain; 5Psychiatry and Mental Health Research Group, Instituto Investigación Sanitaria Valdecilla (IDIVAL), Santander, Spain; 6Centre of Mental Health Lorca, Lorca, Murcia, Spain; 7Department of Psychiatry, General Hospital de Villarrobledo, Villarrobledo, Albacete, Spain; 8Department of Psychiatry, Los Arcos-Mar Menor University Hospital, San Javier, Murcia, Spain; 9Department of Psychiatry, Alcanyis General Hospital, Xátiva, Valencia, Spain; 10Department Psychiatry, Infanta Elena University Hospital, Madrid, Spain; 11Department of Psychiatry, San Cecilio Clinic Hospital, Granada, Spain; 12Centro de Investigación Biomédica en Red en Salud Mental (CIBERSAM), Instituto de Salud Carlos III, Sevilla, Spain; 13West London National Health System (NHS) Trust, London, UK; 14Department of Brain Sciences, Imperial College of London, London, UK; 15Department of Neurology, Santa Lucía University Hospital, Cartagena, Murcia, 30202, Spain; 16Group of Clinical and Experimental Pharmacology, Institute for Biomedical Research of Murcia (IMIB), Murcia, Spain; 17Faculty of Pharmacy and Nutrition, San Antonio Catholic University of Murcia (UCAM), Murcia, Spain*These authors contributed equally to this workCorrespondence: Juan Antonio García-Carmona, Department of Neurology, Santa Lucía University Hospital, C/Mezquita s/n 30202, Cartagena, Murcia, Spain, Tel/Fax +34 968 110 859, Email dr.jagarcar@gmail.comBackground: Patient satisfaction and perceived treatment effectiveness play a critical role in healthcare outcomes and overall well-being. Understanding patient experiences can help identify barriers to adherence and guide improvements in therapy. Previous studies, such as those conducted with PP3M and PP1M, have highlighted the importance of patient satisfaction in optimizing the management of chronic conditions, demonstrating that satisfaction is linked to better adherence and overall treatment success. Nonetheless, there was no data available with patients treated with paliperidone 6-month (PP6M). Therefore, we aimed to evaluate the perspectives, including the perceived effectiveness and satisfaction of patients, their relatives and mental health professionals on the twice-yearly treatment with PP6M in usual clinical practice.Methods: The cohort of patients derived from the P2Y study. This is a multicenter, prospective study across different sites in Europe. Patients, relatives and psychiatrists were asked for satisfaction, by using the Medication Satisfaction Questionnaire (MSQ), and perceived effectiveness. We included all patients who were initiated or switched to PP6M and completed one year of treatment.Results: A total of 233 patients were included in this study, of which 9 (4%) discontinued PP6M at 12 months. Most patients were male (69%, 160 participants), 66% (156 patients) carried a diagnosis of schizophrenia and 16% (38 patients) of comorbid substance use disorder. Furthermore, 22% (51 patients), 70% (164 patients) and 8% (19 patients) were treated with PP1M, PP3M and other oral/LAIs antipsychotics, respectively. The majority of patients (81.5%, n = 190/233), relatives/carers (81.1%, n = 189/233) and clinicians (90.9%, n = 212/233) were extremely satisfied, very satisfied or satisfied 1 year after switching from PP1M, PP3M and other antipsychotic to PP6M with similar findings between patients diagnosed with schizophrenia and other diagnoses. Last, 42% of patients, 45% of their relatives and 40% of clinicians perceived PP6M as more effective compared to the previous treatment. In contrast, only 3% of patients, relatives and clinicians perceived PP6M as less effective.Conclusion: Patients, their carers and relatives as well as mental health professionals reported a high satisfaction rate with PP6M, and equally good or even better perceived effectiveness compared to PP1M, PP3M or other oral or LAIs antipsychotics in the majority of cases. Improved patient experience with PP6M could improve treatment continuity and reduce hospitalization rates.Keywords: paliperidone-palmitate 6-monthly, schizophrenia, long-acting injectable antipsychotics, patient satisfaction, psychiatrists and family perspectives, effectiveness